Is flourishing good for the heart? Relationships between positive psychology characteristics and cardiorespiratory health - Konkoly Thege, Barna; Tarnoki, Adam D.; Tarnoki, David L.; Garami, Zsolt; Berczi, Viktor; Horvath, Ildiko; Veress, Gabor (Anales de Psicología / Annals of Psychology, 2014)
The purpose of this study was to provide further data on the relationships between positive psychology constructs and cardiorespiratory parameters including arterial stiffness indicators. Hypotheses were tested cross-sectionally on a sample of patients with cardiovascular disease and on a healthy sample. Life satisfaction, psychological well-being, optimism, meaning in life, and sense of coherence were included as psychological indicators, while peripheral and central blood pressure, arterial stiffness, and heart cycle and respiratory function parameters were used as physiological variables. Most of the associations examined were not significant in either sample, with some notable exceptions (the direction of these linear relationships was in accordance with our expectations). Satisfaction with life was related to lower peripheral systolic and mean arterial blood pressure in the clinical sample. Further, sense of coherence was positively associated with forced expiratory volume. In the healthy sample, the augmentation indexes and aortic systolic blood pressure were negatively associated with optimism. However, none of the linear and non-linear relationships proved to be significant in either of the samples when using the Bonferroni correction. Further research should determine whether the present findings derive from the cultural characteristics of our samples or whether the mediators between flourishing and cardiorespiratory health should be sought among other variables than the ones included in the present investigation